2015
DOI: 10.1111/evj.12431
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils in the management of the donkey louse, Bovicola ocellatus

Abstract: These results demonstrate that the inclusion of essential oil suspensions during grooming can be used to manage louse populations successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Both preclinical and clinical studies considered in this review revealed promising ovicidal and pediculicidal activities for TTO against head and body lice. Several reports from laboratory and animal studies investigating TTO (1-20%) for the treatment of Bovicola ocellatus lice-infested donkeys [135][136][137][138] and Bovicola ovis lice-infested sheep [139,140] also showed promising efficacy with mortality rates in the range of 78-100%, verifying the findings from human studies. Three species of lice are known to parasitise humans: the head louse (Pediculus humanus capitis), the body louse (P. humanus humanus), and the crab or pubic louse (Pthirus pubis) [9,141].…”
Section: Insecticidal Activity Of Tto and Its Components Against Licesupporting
confidence: 64%
“…Both preclinical and clinical studies considered in this review revealed promising ovicidal and pediculicidal activities for TTO against head and body lice. Several reports from laboratory and animal studies investigating TTO (1-20%) for the treatment of Bovicola ocellatus lice-infested donkeys [135][136][137][138] and Bovicola ovis lice-infested sheep [139,140] also showed promising efficacy with mortality rates in the range of 78-100%, verifying the findings from human studies. Three species of lice are known to parasitise humans: the head louse (Pediculus humanus capitis), the body louse (P. humanus humanus), and the crab or pubic louse (Pthirus pubis) [9,141].…”
Section: Insecticidal Activity Of Tto and Its Components Against Licesupporting
confidence: 64%
“…Independently of the botanical products investigated, the majority of the studies were focused on essential oils, that is, as already observed for other vectors as mosquitoes [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and ticks [ 25 , 26 , 29 ]. Essential oils were the formulation that provided the more interesting results.…”
Section: Discussionmentioning
confidence: 99%
“…From these precursors, several synthetic insecticides and repellents have been developed in the last decades; used alone or in combination, they have contributed to the protection of humans and animals against insects and the related VBDs. However, the wide and unprejudiced use of these formulations have led to the loss of their effectiveness and the development of resistance phenomena [ 25 , 26 ]. Moreover, considering the restrictions on the use of some insecticides and repellents because of their effects on both animal and human health [ 27 ] as well as on the environment [ 28 ], the search for natural repellents as an alternative to chemical-based products has been pushed forward in the last years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chewing lice may be removed with a topical application of cypermethrin, but in many donkeys lice have become resistant to permethrins (Elise and others 2012). In these cases, a topical 5 per cent tea tree oil product can be efficacious (eg, Equine Nit Nat [AgriEnt], which was developed in collaboration with the Donkey Sanctuary) (Elise and others 2016). Tea tree oil can be an irritant if used on broken skin and so it is best applied as a preventive measure.…”
Section: The Pruritic Donkeymentioning
confidence: 99%